Twitter Versus the Traditional Media: A Survey Experiment Comparing Public Perceptions of Campaign Messages in the 2016 U.S. Presidential Election. (August 2018) - Morris, David S.
In the 2016 U.S. presidential campaign, both the traditional media and social media platforms, like Twitter, were critical in attempts to influence voters. Prior to the 2016 presidential election, the assumption was that campaign messages sent through the traditional media are perceived as more effectual by the public than those sent via Twitter. But after the election of Donald Trump, there is now a sense that things may have changed. In this new era of American politics and campaign discourse, do campaign messages sent via Twitter resonate equally with messages sent through the traditional media? This study attempts to address this question by utilizing a survey experiment to test whether campaign messages sent using USA Today headlines were perceived as more believable and persuasive by potential voters than messages sent via Twitter. The results suggest that campaign messages about candidates sent via Twitter—regardless of the candidate of focus—resonate just as strongly with potential voters as those sent via the traditional media. This provides a potential partial explanation for the shocking rise of Donald Trump's political fortunes.